A systematic review of emerging contaminants in the Greater Bay Area (GBA), China: Current baselines, knowledge gaps, and research and management priorities. Issue 131 (May 2022) - Cundy, A.B.; Rowlands, F.M.; Lu, G.; Wang, W.-X.
Abstract: Development of the Greater Bay area, China (GBA) has imposed significant pressures on ecosystems within the wider Pearl River Delta (PRD) system, including through inputs of contaminants from the GBA's rapidly expanding urban, industrial and agricultural activities. Here, we assess publication trends, sampling focus, and concentrations observed for a range of emerging contaminants (pharmaceutical and personal care products, pesticides, other endocrine disrupting chemicals, platinum group elements, and microplastics) in the GBA, via a systematic review of papers (n = 407) indexed in Science Direct, SpringerLink and Wiley Online databases. While emerging contaminants form the focus of increasing numbers of publications since 2006, they are understudied compared to more traditionally-measured contaminants (here, DDT and polycyclic aromatic hydrocarbons, PAHs). BisphenolA was the most widely studied of the emerging contaminants (n = 41 studies) in the GBA, followed by macrolides (n = 32 studies). While multiple point measurements with high precision and low detection limits have been reported for various emerging contaminants, these have not been integrated for management purposes. A relatively high percentage of studies present data from single deployments (48% of studies, despite strong seasonality in the PRD system), data coverage is variable spatially, and reported contaminant concentrations vary significantly (over one to four orders of magnitude). We assess the currently published knowledge under the Source-Pathway-Receptor contaminant linkage model and use this to identify (a) current research emphasis in relation to assessment of contaminant risk, and (b) key knowledge gaps around sources, pathways and receptors in the GBA system. Graphical Abstract: ga1 Highlights: A systematic review was performed on emerging contaminant data from the GBA, China. Emerging contaminants are understudied compared to "traditional" contaminants. Key knowledge gaps remain around sources, pathways and receptors. Available data do however provide a baseline dataset to inform future studies.